Accessibility and inclusion of people with autism spectrum disorder in science museums in Rio de Janeiro/Brazil - Pereira, Grazielle Rodrigues; Moniz, Ana Lucia de Albuquerque; Lima, Helena Cunha de Paula; Henrique, Rosália do Nascimento Silva; Alves, Gustavo Henrique Varela Saturnino; Fragel-Madeira, Lucianne; Henrique-Junior, Sérgio de Souza (Frontiers in Education, 2025)
This work aimed to identify the perceptions and experiences of mediators and mediation team leaders of four science museums in Rio de Janeiro/Brazil, regarding the accessibility and inclusion of people with Autism Spectrum Disorder (ASD). The research was conducted in four science museums in the state of Rio de Janeiro: Espaço Ciência Viva, Casa da Ciência, Memorial Carlos Chagas Filho, and Espaço Ciência InterAtiva. The data was collected through semi-structured interviews focused on the experiences and perceptions about the accessibility and inclusion of people with ASD. Three managers of mediation teams and nine mediators, in a total of 12 participants. The results show the need to offer specific training for the mediators when attending to the public with ASD, as well as the implementation of inclusive practices and communicational and attitudinal accessibility strategies. We can conclude that, although there are punctual initiatives, there is a need for changes and the implementation of practices to make museums accessible and welcoming spaces committed to the inclusion of people with ASD.